Kształtowanie się polskiego modelu wykonywania tymczasowego aresztowania w latach 1945−1969 - Kwieciński, Adam; Pałaszewski, Piotr (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
This publication aims to show the evolution of the statute related with the performance of the strictest preventive measures. The analysis covers the period from the end of World War II until the legislation of the first Polish Executive Penal Code. Explorationof research concerned the most important legal and other acts specifying the status of the person against whom preventive detention is enforced. There are also presented the statistics related to preventive detention during this period.
Keywords: areszt prewencyjny; środki zapobiegawcze; tło historyczne; stan prawny; penitencjarność; postępowanie egzekucyjne